Utilização da hemoglobina como novo marcador biológico do linfonodo sentinela em ratas wistar - Alves, Mayara Maia (2018)
Epidemiological studies do not provide conclusive evidence justifying the recommendation of specific prevention strategies. Thus, efforts to improve the numbers related to breast cancer are directed towards the early diagnosis, resulting in a decrease of administrative treatment aggressiveness and a mortality rate reduction. Sentinel lymph node (SLN) biopsy, in breast cancer surgical treatment as initial staging, has been currently employed as part of the routine protocol, avoiding in most cases the total lymphadenectomy. To make it possible to do SLN biopsy, it is necessary to use markers that identify the SLN and facilitate the surgical procedure. Among the most used markers are Technetium and Blue patent. The results of sentinel lymph node research are encouraging. However, the use of its markers has disadvantages, such as the high cost of technetium and allergic reactions caused by patent blue. During the physical examination of two patients submitted to breast biopsy, it was observed, in their skin, the mapping of the lymphatic vessels with a reddish coloration, towards the axillary lymph node. Previous studies have disseminated the theory that a blood derivative (Hemosiderin) can be captured by macrophages and accessed in the lymphatic duct towards the armpit. In an attempt to replicate what was seen in patients, an experimental protocol was developed to obtain a blood-derived marker and was tested in a dogs model of experimental surgery, where was proved the existence of a new autologous blood marker. After several preliminary studies, procedures were performed in patients with breast cancer at Hospital Maternidade Escola Assis Chateaubriand, localized in Fortaleza-CE. These procedures with Hemosiderin were a success. However, the hypothesis that the blood-derived marker was hemosiderin emerged only from clinical data and preliminary scientific research, so this assertion has its discord. This project studied the characteristics of the blood derived (Hemosiderin), leading to clarification of the main substance responsible for SLN marking and isolated biological marker improvement. It was analyzed in parallel with Pre-clinical studies in wistar rats, by purifying the substance responsible for marking and standardizing its drainage time, dosing, methemoglobin concentration, and how the proteolytic enzymes and temperature could interfere with. After study, it was observed that hemoglobin is the main responsible for SLN marking. This marking process could be optimized by standardizing the biological marker homeostatic conditions, applying to the hemoglobin concentrate 3% nitrite for 48 h and protease inhibitors, respecting the 2h drainage time and maintaining the sample temperature at 25 °C.